Innovative business activity in process of implementing «triple helix» model of Henry Itskovich - Yu. I. Rastova; D. A. Stepanenko (Омский научный вестник: Серия "Общество. История. Современность")
The study of the interaction of the state, universities and business is carried out, the specifics of the interaction of the elements of the “triple helix” in Russia are revealed. Conclusions are drawn about the weak development of the business spiral and the uncertain role of universities in the model of innovative activity. The analysis of the dynamics of the Global Innovation Index and sub-indices is carried out and the weak development of interaction within the framework of innovation clusters, strategic alliances and the low level of R&D funding is revealed. Based on the analysis of the opportunities and limitations of large and small businesses, directions are proposed for increasing the innovative activity of the region